THE ATTITUDE OF PEOPLE TOWARDS WORK PERFORMANCE ON SOCIAL DEVELOPMENT ASPECT OF SINJAROEN SUB DISTRICT, ADMINSTRATIVE ORGANIZATION, PHRASANG DISTRICT, SURAT THANI PROVINCETHAMMARAT MUNICIPALITY - Chosom , Supawadee; Nuthongkaew, Kantaphon (Journal of Buddhist Anthropology, 2020)
The purpose of this research is to compare and study the problems and recommendations. And solutions People’s Attitudes towards Social Development Administration of Sincharoen Subdistrict Administrative Organization, Phrasaeng District, Surat Thani Province This research Using quantitative research methods The sample consisted of 368 households. Systematic random sampling method The research instruments were questionnaires for instrument quality checking. The Cronbach’s alpha coefficient was 0.92. The quantitative data was analyzed by descriptive statistics such as percentage, mean, standard deviation. The results of the research revealed that 1) The people have attitudes towards the social development administration of Sincharoen Subdistrict Administrative Organization, Phrasaeng District, Surat Thani Province, in total, 5 aspects are at the high level as for politics ( = 3.68) and government Is the highest level ( = 3.74). 2) The results of the comparison of the attitudes towards the social development administration of Sincharoen Subdistrict Administrative Organization, Phrasaeng District, Surat Thani Province of the people with different gender, age, education level, were different. Differences were statistically significant at the .001 level, while the different occupations were not significantly different at the .05 level. 3) Suggestions about problems For feedback The attitude of the people towards the social development administration of Sincharoen Subdistrict Administrative Organization, Phrasaeng District, Surat Thani Province in the high level ( = 3.59) is the economy. Group in the form of a career group that is not good enough and should support the development of the structure There are not many basic public utilities that are essential to life.